Language Learning Strategies of EFL College Students - Dewi Furwana (Universitas Cokroaminoto Palopo, 2017)
The objectives of the research were (1) to investigate the most dominant language learning strategies (LLS) used by sixth semester students of English Department of Tarbiyah Faculty at UIN Alauddin Makassar and (2) to find out the differences of using LLS between high achieving students and low achieving students. The result of the quantitative data through questionnaire showed that (1) metacognitive strategies was the most dominant LLS used, and (2) the high achieving students used metacognitive strategies with the highest preference and low achieving students used compensation strategies with the highest preference. The result of the qualitative data through think aloud showed that (1) the most dominant LLS employed by students were listening music, utilizing time for practicing and self-evaluating, (2) the most dominant LLS used by high achieving students were utilizing time for practicing, practicing English together and self-evaluating, whereas the most dominant LLS used by low achieving students were listening music, asking friend and selecting topic. The data were collected through documentation used to classify high achieving students and low achieving students based on their grade point average. It is concluded that the most dominant language learning strategies employed by students was metacognitive strategies. High achieving students employed different strategy than low achieving students. High achieving students used learning strategies more frequently than low achieving students.